(1045) دوال الطلب للاقطان المصريه طويله التيله الممتازه فى الاسواق المحليه وبعض الاسواق العالميه Demand figures for premium long-staple Egyptian cotton in local markets and some international markets - محمد محمود رزق ، محمد كامل ريحان (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة البحثية الصادرة عن معهد التخطيط القومي دراسة قياسية متخصصة لتحديد "دوال الطلب للأقطان المصرية طويلة التيلة الممتازة" في الأسواق المحلية وأبرز الأسواق العالمية كالهند والمملكة المتحدة وألمانيا الغربية وفرنسا. وتستعرض الدراسة الأهمية الاستراتيجية الكبرى للقطن المصري في البنيان الاقتصادي للدولة بوصفه مصدراً أساسياً للدخل القومي والعملات الأجنبية، ومادة خاماً حيوية لصناعة الغزل الرفيع والمنسوجات الفاخرة التي تلبي الطلب المحلي والعالمي. ويوضح البحث الموقف الاحتكاري والتنافسي في السوق الدولي؛ حيث تهيمن مصر والسودان وبيرو والولايات المتحدة على أكثر من 95% من الإنتاج العالمي للأقطان طويلة التيلة الممتازة، مع الإشارة إلى تراجع الأهمية النسبية لمصر بمرور الوقت نتيجة اشتداد المنافسة الدولية، لا سيما من جانب السودان، مما يستدعي التنسيق التسويقي المشترك والتخطيط الزراعي السليم للموازنة بين إنتاج القطن التصديري وإنتاج الحبوب الغذائية. This research memorandum issued by the Institute of National Planning presents an econometric study aimed at determining the demand functions for Egyptian extra-long staple cotton in both domestic markets and major international markets, including India, the United Kingdom, West Germany, and France. The study highlights the major strategic importance of Egyptian cotton within the country’s economic structure, as it represents a key source of national income and foreign exchange, as well as a vital raw material for fine spinning and luxury textile industries that serve both domestic and international demand. The study also examines the monopolistic and competitive structure of the international market, where Egypt, Sudan, Peru, and the United States account for more than 95% of global production of extra-long staple cotton. It further notes the gradual decline in Egypt’s relative importance over time due to increasing international competition, particularly from Sudan. This situation calls for coordinated marketing efforts and sound agricultural planning to balance export-oriented cotton production with the production of food grains.